The Role of Teachers in Supporting Students' Psychological Health in the Era of Digital Transformation - Wayan Gastiadirrijal; Moch Alief ‘Izzulhaq; Nurti Budiyanti (MASALIQ, 2026)
The proliferation of digital platforms and social media amid rapid technological transformation is profoundly reshaping students’ psychological dynamics, including emotional regulation, learning motivation, self-concept, and social interactions, thereby generating both opportunities and risks for schooling. This qualitative study synthesizes findings from a systematic literature review and case studies from Indonesian secondary schools to examine teachers’ roles in mitigating digital-era psychological risks while simultaneously leveraging digital affordances. The analysis integrates empirical evidence on social media’s dual impact, showing that positive effects include enhanced access to knowledge and the stimulation of fine-motor creativity, whereas risks encompass heightened anxiety, fear of missing out (FOMO), addictive usage patterns, and reduced gross motor activity. Across the reviewed studies and cases, teachers emerge as pivotal facilitators who apply educational psychology principles, such as cooperative learning, emotion regulation training, and constructive feedback to strengthen students’ resilience, with collaborative interventions involving counselor–parent partnerships contributing to the reduction of emotional distress. Strengthening digital literacy, regulating screen time, and designing balanced learning environments are identified as essential conditions for sustaining students’ psychological well-being. The study concludes that targeted teacher training in digital emotional intelligence and culturally adaptive pedagogical strategies, particularly within Islamic education contexts, is crucial for supporting holistic student development in increasingly hyper-connected educational ecosystems.